Assessing the impact of a sex education program in primary education - Pedro Miguel Ferreira; Marisalva Fávero; Amaia DelCampo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
This study intended to evaluate a sex education program (SEC) for the students of third grade, which was prepared according to directions of the law 60/2009 in Portugal. The SEC program consists of five sessions. For the evaluation of the program it had been used a qualitative methodology based on interviews before and after application on a sample of students aged 8 and 9 years old: 16 students from the experimental group (participants of the ESC) and 11 from the control group. The interviews were analyzed by content analysis. Before implementing the program, both groups had some knowledge in the area of sexuality. In the other hand, had misconceptions and numerous gender stereotypes. After the SEC application, it was found an increase in knowledge in the experimental group, compared with the control group, but in both groups, gender stereotypes persist. The results indicate that the sex education Portuguese law is unable to point the specific needs of this age group, by not to stressing the importance of working in the sex education programs for the first cycle the gender stereotypes and therefore, gender inequalities.